2020
DOI: 10.1111/famp.12536
|View full text |Cite
|
Sign up to set email alerts
|

Joint Physical Custody and Adolescents’ Life Satisfaction in 37 North American and European Countries

Abstract: Joint physical custody, a parental care arrangement in which a child lives with each parent about equally after separation or divorce, is an increasingly common phenomenon in many Western countries. Although attention from family scholars, practitioners, and law professionals is growing, there are hardly any numbers on the prevalence of joint physical custody (JPC). Moreover, studies using large‐scale representative data on the effects of JPC for children’s well‐being are still rare. The data for this study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 59 publications
7
42
0
2
Order By: Relevance
“…A large study of 184,496 school-aged children found that life satisfaction was decreased when either parent was absent, but where the father was absent the effect was attenuated when accounting for perceived family affluence [81]. A follow-up to this study, incorporating additional cohorts, also reported similar effects [82]. The present study found no effect of having a lone parent on MDD or BRS and there were no significant associations with any of the CpG sites analysed.…”
Section: Discussionsupporting
confidence: 54%
“…A large study of 184,496 school-aged children found that life satisfaction was decreased when either parent was absent, but where the father was absent the effect was attenuated when accounting for perceived family affluence [81]. A follow-up to this study, incorporating additional cohorts, also reported similar effects [82]. The present study found no effect of having a lone parent on MDD or BRS and there were no significant associations with any of the CpG sites analysed.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, all previous research on this topic is limited to Norway and Sweden-two countries in which the prevalence of joint physical custody is comparatively high (30% of all post-separation families in Norway (Kitterød and Wiik 2017) and 40% in Sweden (Fransson et al 2018a)). Consequently, this analysis is the first study to examine the association between joint physical custody and children's psychosomatic health with data from a country where the numbers of joint physical custody families remain relatively low (Steinbach et al 2021), with only 4% to 5% of all post-separation families practicing this new physical custody arrangement (Walper 2016;Walper et al 2020).…”
Section: The Present Studymentioning
confidence: 99%
“…This is a major shift away from sole physical custody (SPC) arrangements, in which the mother typically takes care of the children after family dissolution. In Germany, JPC families make up about 5% of all post-separation families and are thus not yet widespread (for an overview of prevalences of JPC in North American and European countries, see Steinbach, Augustijn, et al, 2020a). A reason for the low prevalence of JPC might be that although all German families receive support from the state independently of their child custody arrangement, majority attitudes in Germany regarding family responsibilities still quite traditionally see the mother as the primary family caregiver (Kan et al, 2011).…”
Section: Conclusion: Empirical Investigations Of Children In Post-sepmentioning
confidence: 99%
“…In total, 1,554 families participated in the FAMOD study. Because JPC is still very rare in Germany (Steinbach, Augustijn, et al, 2020a), and because there is no way to identify these families in any official German statistics, we had to use an unconventional, creative approach to data collection. Thus, the respondents were recruited with the help of 232 professional interviewers from Kantar Public, who had worked in every part of Germany, from small villages to big cities.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation